2008
DOI: 10.1159/000152868
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Onion (<i>Allium cepa</i> L.) in a High-Fat Diet Streptozotocin-Induced Diabetes Rodent Model

Abstract: Background/Aims: The present study was conducted to investigate the effects of two dietary doses of freeze-dried onion powder on diabetes-related symptoms in a high-fat (HF) diet streptozotocin (STZ)-induced diabetes rat model. Methods: Five-week-old male Sprague-Dawley rats were fed a HF diet for 2 weeks and then randomly divided into 4 groups as follows: HF control (HFC), diabetic control (DBC), onion low (ONL; 0.5%) and onion high (ONH; 2.0%). Diabetes was induced by an intraperitoneal injection of STZ (40 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(16 citation statements)
references
References 60 publications
1
15
0
Order By: Relevance
“…HFD usually results in obesity leading to insulin resistance, whereas low dose of STZ causes moderate destruction of insulin secretion [23]. …”
Section: Discussionmentioning
confidence: 99%
“…HFD usually results in obesity leading to insulin resistance, whereas low dose of STZ causes moderate destruction of insulin secretion [23]. …”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the energy value of onion is not significant (~40 kcal/100 g) [13]. Most importantly, onions were found to contain several and unique phytochemicals such as quercetin and quercetin glucosides, kaempferol, thiosulfinates, cepaenes, anthocyanins, and sulfur compounds (e.g., S-methyl cysteine sulfoxide, diallyl trisulfide, S-allyl cysteine sulfoxide, dimethyl trisulfide) that have been identified to have an impact on humans’ health [14,15]. Yet, some of these phytochemicals are under basic and translational research to explore their possible biological effects in humans.…”
Section: Introductionmentioning
confidence: 99%
“…[12] Recently, it was shown that the consumption of onions has positive effects that reduce the risks for various diseases, including many forms of cancer, vascular and heart diseases, diabetes, and ischemia. [1314151617] Pretreatment of Swiss albino mice with the methanolic extract of the outer scales and edible portion of the onion remarkably attenuated ischemia/reperfusion-induced cerebral infarct size and prevented ischemia/reperfusion-induced impairment of short-term memory and motor incoordination. This study concluded that the methanolic extract of the outer scales and edible portion of the A. cepa bulb scavenged ROS and that the anti-oxidative effect of the extract attenuated global cerebral ischemia/reperfusion-induced cerebral injury.…”
Section: Introductionmentioning
confidence: 99%